Costa Rica : Report on the Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses observance of standards and codes-data Module in Costa Rica, response by the authorities, and detailed assessment using the Data Quality Assessment Framework. The assessment reveals that all statistical agencies get high marks in assurances of integrity. Macroeconomic statistics are compiled in accordance with strict technical considerations and are disseminated without political interference. There are clear ethical guidelines for public servants. The accuracy and reliability of macroeconomic statistics are generally sound, although source data are limited in all datasets, except for the Monetary and Financial Statistics.